Exploring the Intersection of Isolated-CNS Hemophagocytic Lymphohistiocytosis and Pediatric Chronic Lymphocytic Inflammation With Pontine Perivascular Enhancement Responsive to Steroids. (October 2021) - Debinski, Carly; Goergen, Stacy; McLean, Catriona; Buckland, Michael E.; Kumar, Beena; Tiller, Georgina; Cole, Theresa; Ojaimi, Samar; Fahey, Michael
CLIPPERS (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) is an extremely rare neurologic inflammatory condition. Fewer than 10 pediatric cases have been described. Debate persists as to whether it is a distinct disease or a clinical, radiologic, and histologic phenotype evolving into another disorder. We propose that CLIPPERS may be a clinical manifestation of an underlying state of immune-dysregulation. We describe the case of the youngest known report of CLIPPERS, an 18-month-old infant from Melbourne, Australia. Reviewing the literature for all reported pediatric cases, we identified that robust investigation and whole exome sequencing was underutilized and proposed diagnostic criteria were frequently unmet. Particular focus should be paid to genes known to cause familial hemophagocytic lymphohistiocytosis (HLH), with the CLIPPERS phenotype manifesting as a form of isolated central nervous system (CNS)-HLH in some patients. Curative treatment options such as hematopoietic stem cell transplantation may be appropriate for some patients and should be considered early.